Spend Now, Pay Later? : Tax Smoothing and Fiscal Sustainability in South Asia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper tests a version of Barro's tax-smoothing model, which assumes intertemporal optimization by a government seeking to minimize the distortionary costs of taxation, using Pakistan and Sri Lankan data for 1956-95 and 1964-97, respectively. The empirical results indicate that Pakistan's fiscal behavior is consistent with tax smoothing, but not Sri Lanka's. Moreover, fiscal behavior in both countries was dominated by a stagnation of revenues, large tax-tilting-induced deficits, and the consequent accumulation of excessive public liabilities. Analysis of the time-series characteristics of tax-tilting behavior indicates that for both countries the stock of public liabilities is unsustainable under unchanged fiscal policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet